Smart Agricultural Machinery and Mechanization: A Review of Automation, Precision Farming, and Emerging Technologies - Ghazi, Naz M.; Othman, Skala S (American Journal of Biology and Natural Sciences, 2026)
The emergence of smart agricultural machinery has become one of the key aspects of modern agricultural mechanization driven by the development of automation and precision agriculture technologies along with sensor systems and artificial intelligence. This review provides a thorough synthesis of the technological development of agricultural machineries and how it has been integrated with intelligent systems of operation enabling data-driven, adaptive, and efficient operations of the field. The review examines automation and guidance systems development, precision farming technologies, sensors-based data collection, and artificial intelligence and machine learning use in agricultural machineries. The important issues regarding integration of the system, quality of data, economic viability, and adoption are also discussed. The data highlights the role of smart agricultural machinery as a key aspect of improving the efficiency of operations, resource management, and ensuring sustainability in the contemporary agriculture. Constant studies and responsible use of new technologies must be mandatory in order to achieve the maximum potential of intelligent mechanization of future agricultural systems.